Pengaruh Work Life Balance, Family Supportive Supervisor Behaviour, dan Kepuasan Kerja Terhadap Kinerja Karyawan - Azaria Maharani, Nova; Purwo Saputro, Edy (Universitas Muhammadiyah Surakarta, 2023)
This study conducted to analyze the impact of work life balance, family supportive supervisor behavior, and job satisfaction towards employees performance. The method used in this paper is quantitative method. The data were collected by using questionnaire with measured responses through five point of Linkert scale. Furthermore, this study employed application named SPSS version 22 to help in analyzing the data. The respondents of this study are the employees of PT. Sapta Sari Tama in Surakarta branch with 40 employees as the total population. The result of this study as follows, that Work Life Balance made a significantly positive impact towards employees performance, meanwhile Family Supportive Supervisor Behavior made a negative impact and insignificant towards employees performance, and Job Satisfaction positively impact and significant towards employees performance.